2008
DOI: 10.1152/ajpregu.90646.2008
|View full text |Cite
|
Sign up to set email alerts
|

Neural and cardiovascular responses to emotional stress in humans

Abstract: Sympathetic neural responses to mental stress are well documented but controversial, whereas sympathetic neural responses to emotional stress are unknown. The purpose of this study was to investigate neural and cardiovascular responses to emotional stress evoked by negative pictures and reexamine the relationship between muscle sympathetic nerve activity (MSNA) and perceived stress. Mean arterial pressure (MAP), heart rate (HR), MSNA, and perceived stress levels were recorded in 18 men during three randomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 23 publications
2
52
0
Order By: Relevance
“…First, MSNA responsiveness to mental stress can be widely variable in humans (7). Second, although early evidence suggested that self-perceptions of stress might explain the large interindividual variability associated with MSNA reactivity to mental stress (4), more recent studies have challenged this paradigm (6,9). Third, and perhaps most importantly, our laboratory has documented a dissociation between MSNA and blood pressure (BP) reactivity to mental stress in young, healthy adults (9).…”
Section: Subjects With a Family History Of Hypertension (Fhh) Demonstmentioning
confidence: 99%
“…First, MSNA responsiveness to mental stress can be widely variable in humans (7). Second, although early evidence suggested that self-perceptions of stress might explain the large interindividual variability associated with MSNA reactivity to mental stress (4), more recent studies have challenged this paradigm (6,9). Third, and perhaps most importantly, our laboratory has documented a dissociation between MSNA and blood pressure (BP) reactivity to mental stress in young, healthy adults (9).…”
Section: Subjects With a Family History Of Hypertension (Fhh) Demonstmentioning
confidence: 99%
“…In all cases, blood pressure increased between baseline and mental stress [12]. Accordingly, the influence of mental work on sympathetic nervous activity remains equivocal and differences in the sympathetic baroreflex sensitivity to blood pressure elevation [39] or a greater effect of the perceived stress level than the mental stress itself [14] could explain these discrepancies.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Dittmar et al [23] reported that for a similar mental work intensity, women perceived the workload to be more mentally challenging than men, and the latter is associated with a more important stimulation of the cardiovascular response in healthy subjects [14]. In our study, the intensity of mental work did not differ between men and women, as characterized by the NASA-Task Load Index score and the reaction time to a secondary task, which supports a recent study by Persson et al [21], where they observed no difference in cortisol, adrenaline, noradrenaline, heart rate activation and perceived stress level between men and women with identical job tasks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, emotional stress differs from mental stress. This was explored in the December 2008 issue of the American Journal of Physiology by Carter and colleagues, from the Department of Exercise Science at Michigan Technological University, USA [2]. They recorded muscle sympathetic nerve activity (MSNA), heart rate and blood pressure in subjects exposed to neutral or negative images, or to mental stress.…”
Section: It's Just Emotion Taking Me Overmentioning
confidence: 99%